2006
DOI: 10.1364/oe.14.001658
|View full text |Cite
|
Sign up to set email alerts
|

The effect of higher-order dispersion on slow light propagation in photonic crystal waveguides

Abstract: We have studied the dispersion of ultrafast pulses in a photonic crystal waveguide as a function of optical frequency, in both experiment and theory. With phase-sensitive and time-resolved near-field microscopy, the light was probed inside the waveguide in a non-invasive manner. The effect of dispersion on the shape of the pulses was determined. As the optical frequency decreased, the group velocity decreased. Simultaneously, the measured pulses were broadened during propagation, due to an increase in group ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
68
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(70 citation statements)
references
References 2 publications
0
68
1
1
Order By: Relevance
“…It has long been predicted that the slow light enhancement of light-matter interaction should induce a reduction of either the physical length of waveguide or input power needed to observe nonlinear phenomena such as stimulated Raman scattering or harmonic generation [3,4]. However, demonstrations of such enhancement process are still rare [5] and preliminary, partly due to the challenging increase of coupling loss, linear [6] and nonlinear losses as well as the large high order dispersion that typically cause pulse distortion in the slow light regime [7].…”
Section: Introductionmentioning
confidence: 99%
“…It has long been predicted that the slow light enhancement of light-matter interaction should induce a reduction of either the physical length of waveguide or input power needed to observe nonlinear phenomena such as stimulated Raman scattering or harmonic generation [3,4]. However, demonstrations of such enhancement process are still rare [5] and preliminary, partly due to the challenging increase of coupling loss, linear [6] and nonlinear losses as well as the large high order dispersion that typically cause pulse distortion in the slow light regime [7].…”
Section: Introductionmentioning
confidence: 99%
“…Potentially, PhCWs may facilitate delay lines for package synchronization, dispersion compensation, and enhanced light-matter interactions [2,3] in nanophotonic circuits by exploiting slow-light phenomena [4]. However, the practical utilization of ultra-slow light reaching group velocities below ~c 0 /200 [3,5] in PhCWs may be limited due to an inherent small bandwidth [6], impedance mismatch [7,8], intensified loss mechanisms at scattering centers [9], and extreme dispersive pulse broadening [4,10]. Previously, it has been demonstrated that the dispersion properties of PhCWs can be altered via a structural tuning of the waveguide geometry, typically, by changing the waveguide width or by introducing bi-periodicity [11,12,13].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that both material loss and material gain in the PhCWs restrict the attainable group index and degrade slowlight effects [7,8]. Moreover, the benefits of slow light are typically compromised by significant group velocity dispersion (GVD) [9] and concomitant propagation losses [10,11].…”
Section: Introductionmentioning
confidence: 99%